English vs. German from a textual perspective: Looking inside chain intersection - Kunz, Kerstin; Lapshinova-Koltunski, Ekaterina (Bergen Language and Linguistics Studies, 2018)
This paper presents a cross-lingual corpus-based study on the intersection of chains of coreference and lexical cohesion. The two types of cohesion are often combined and thus play an important role for the development of discourse topics. We analyse chain intersection as cases where chain elements of lexical cohesion occur inside of coreference chains. We use a corpus of English and German original texts from four written and spoken registers which is annotated for both types of cohesion. Our analyses point to contrasts between the two languages and across the four registers under analysis in the types and the number of intersections in coreference chains. This variation has an effect on the way important topics develop in a text.